2004
DOI: 10.1017/s0021859604003934
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate leaching and N2-fixation in grasslands of different composition, age and management

Abstract: Grass-legume associations may offer a way of improving the N efficiency of dairy farming, but may also have an adverse impact on the environment by increasing leaching losses. Nitrate leaching from four cropping sequences with different grassland frequency and management (long-term grazed, long-term cut, cereals followed by 1 and 2-year grazed leys) were investigated on a loamy sand in central Jutland for both unfertilized grass-clover (perennial ryegrass (Lolium perenne L.)/white clover (Trifolium repens L.))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 27 publications
4
47
0
2
Order By: Relevance
“…The effect of the age of the ley on the N leaching risk was insignificant in our experiments, which agrees with the findings of Hansen et al (2005) and Eriksen et al (2004). The mineral N level in soil at a depth of 60-90 cm was quite low, less than 5 kg ha -1 in Juva, indicating low N leaching risk.…”
Section: Nitrogen Leaching Risksupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of the age of the ley on the N leaching risk was insignificant in our experiments, which agrees with the findings of Hansen et al (2005) and Eriksen et al (2004). The mineral N level in soil at a depth of 60-90 cm was quite low, less than 5 kg ha -1 in Juva, indicating low N leaching risk.…”
Section: Nitrogen Leaching Risksupporting
confidence: 91%
“…The decrease in the yield and BNF (i.e. N content) of 2-to 8-yearold grass-clover ley led to decreased N leaching in studies of Eriksen et al (2004), but Hansen et al (2005) did not find any significant difference in N leaching after 1-or 10-year-old grass-white clover ley. This indicates that organic N mineralises more easily the younger the perennial plants are.…”
Section: Introductionmentioning
confidence: 79%
“…In 1994 and 1995, the N 2 fixations were estimated as 232 and 408 kg N ha À1 year À1 , respectively (Søegaard et al, 2001), and in 1997 and 1998 as 263 and 124 kg N ha À1 year À1 , respectively (Hansen and Vinther, 2001). In 2001, the N 2 fixation was estimated as 101 kg N ha À1 year À1 (Eriksen et al, 2004). Continuous clover-grass in treatment A increased the SOM content in the simulations from approximately 140 to 143 t C ha À1 in the period of 1995-2003 which corresponds to an increase of 1.9%.…”
Section: Water Balance Doc and Don Leaching Crop Production And Orgmentioning
confidence: 97%
“…Concerning the grasslands it has been found that nutrient leaching is high only from pastures, in cut grassland it is often estimated to be low (Eriksen, Vinther, 2002). Although nutrient leaching from grassland is lower than from arable land it is still important to find opportunities for its reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Bouman et al (2010) showed that in midsummer when the percentage of white clover in the sward is high, N leaching also increases. Eriksen et al (2004) have reported that less leaching occurs from unfertilized grassland containing white clover than from fertilized grass-only grassland. Low and Armitage (1970) studies have demonstrated increased leaching in the swards with reduced legume content.…”
Section: Introductionmentioning
confidence: 99%